2010
DOI: 10.1039/b915573b
|View full text |Cite
|
Sign up to set email alerts
|

MAS-NMR studies of glasses and glass-ceramics based on a clinopyroxene–fluorapatite system

Abstract: Glasses and glass-ceramics based on the ternary system CaMgSi 2 O 6 -NaAlSi 2 O 6 -Ca 5 (PO 4 ) 3 F (diopside(Di)-jadeite(Jd)-fluorapatite(FAp)) have been studied with magic angle spinning (MAS) NMR, powder x-ray diffraction (XRD) and thermal calorimetry. In this silicate system Na 2 O and Al 2 O 3 has been progressively substituted for CaO and MgO: (CaMgSi 2 O 6 ) 1-x -(NaAlSi 2 O 6 ) x -(Ca 5 (PO 4 ) 3 F) y where 0 ≤ x ≤ 30mol% and y = 7 mol%. 29Si MAS-NMR of the glasses showed a peak corresponding to a mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 50 publications
7
23
0
Order By: Relevance
“…Similar results have also been reported on diopside-jadeite-fluorapatite glasses by Abo-Mosallam et al [12]. For the studied glasses, Table 5 gives the theoretically calculated packing density (V t ), the elastic moduli (E cal , S cal and B cal ) and the Poisson's ratio based on the model of Makishima and…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results have also been reported on diopside-jadeite-fluorapatite glasses by Abo-Mosallam et al [12]. For the studied glasses, Table 5 gives the theoretically calculated packing density (V t ), the elastic moduli (E cal , S cal and B cal ) and the Poisson's ratio based on the model of Makishima and…”
Section: Discussionsupporting
confidence: 81%
“…Poisson's ratio exhibits a slight increase at low Al contents, However when we increases the mole % of Jd the network connectivity is increased [12] so the poison ratio decrease, because the higher connectivity of network decrease the Poisson's ratio.…”
Section: Discussionmentioning
confidence: 88%
“…He has reported that with increase in Jd content in the glasses, the polymerization in silicate glass network shifted from Q 2 to Q 3 (Q n : degree of polymerization; n: number of bridging oxygens) and Al exists predominantly as Al (IV) species. A complete solid solution has been reported to exist between Di-Jd glassceramics at 1 atm pressure for the first time in literature [2]. However, to the best of our knowledge, the structure and crystallization behavior in complete series of glasses along DiJd join have not been reported so far in open literature.…”
Section: Introductionmentioning
confidence: 93%
“…Wood et al [9] studied the thermo-chemistry of synthetic Di-Jd pyroxenes and found that the investigated synthetic clinopyroxenes have positive excess enthalpies of mixing. Also, it was reported that Di-Jd solid solutions are 'pseudo-ideal' near 1:1 composition at temperatures of 1000-1500 K. Recently, Abo-Mosallam et al [2] studied the structure and crystallization behavior of glasses www.elsevier.com/locate/ceramint and glass-ceramics along (CaMgSi 2 O 6 ) 1Àx -(NaAlSi 2 O 6 ) x -(Ca 5 (PO 4 ) 3 F) y where 0 x 30 mol.% and y = 7 mol.%. He has reported that with increase in Jd content in the glasses, the polymerization in silicate glass network shifted from Q 2 to Q 3 (Q n : degree of polymerization; n: number of bridging oxygens) and Al exists predominantly as Al (IV) species.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation